From Survival to Solidarity: Sisterhood in the Cinematic Narrative of Pop Star Academy: KATSEYE - Dhia Anaulva Putri; Aquarini Priyatna; Mega Subekti (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2025)
In popular media, women are often portrayed in antagonistic rivalries, reinforcing the narrative that female relationships are inherently competitive. This research explores how Pop Star Academy: KATSEYE, a docu-series documenting the journey of female contestants vying for a spot in a global K-pop girl group, challenges and complicates that narrative by presenting a more nuanced interplay of rivalry and solidarity. While existing scholarship on the Korean Wave (Hallyu) and K-pop has addressed gendered representations and the structural dynamics of the entertainment industry, limited attention has been given to how documentary storytelling mediates these gendered tensions. To address this gap, this study investigates how documentary film can shape, reflect, and potentially disrupt dominant gender ideologies. Employing feminist film analysis, documentary narratology, and close analysis of cinematic techniques, the study demonstrates how Pop Star Academy: KATSEYE constructs a cinematic language of sisterhood that both navigates and subverts the masculine logic of survival shows. Importantly, the study also engages with the cultural and linguistic dimensions of K-pop’s transnational reach, emphasizing how language, performance, and cross-cultural communication inform representations of identity and gender. This intersection of media, language, and culture offers critical insights into the global resonance of female solidarity in contemporary popular culture.